A razoável duração da prisão preventiva: uma análise dos critérios verificadores da dilação indevida - Louback, Cristian Lima dos Santos (2019)
The research examines the fundamental right to a reasonable length of time in the Constitution of the Federative Republic of Brazil of 1988, included in Constitutional Amendment No. 45, dated December 30, 2004 - the so-called Judicial Reform - and its effects within the term of preventive detention . Therefore, in view of the lack of a term of pre-trial detention defined by law, what are the criteria adopted by the Brazilian courts for the definition of undue delay of said pre-trial detention and whether the adoption of such criteria is sufficient for the fundamental right to a reasonable length of criminal proceedings is guaranteed. Given the large number of decisions that may be investigated, it is intended to select, by predetermined criteria, decisions that may reflect the understanding of the Brazilian courts. In order to verify the adoption of the criteria in practice, they will be judged by the Court of Justice of the State of São Paulo, since it is the State that most incarcerates and has the largest prison population, the Superior Court of Justice and the Federal Supreme Court. the upper Courts homelands. It is concluded that, despite the Reform of the Judiciary, implemented by Constitutional Amendment No. 45, of December 30, 2004, introduced in the constitutional text the fundamental right to the reasonable length of the proceedings, both the absence of definition of time limits limiting preventive custody in the criminal procedural law, regarding the lack of adoption of criteria by the courts in the verification of the excessive term of the preventive custody, do not allow the effective exercise of this right, as well as denote traces of the application of the criminal law of the enemy to the provisional prisoners. The hypothetical-deductive approach will be used. The methods of procedure will be comparative and structuralist. In addition, all necessary analysis will be developed based on documental and bibliographical research. The research is developed in the Postgraduate Program in Law of the University of Nove de Julho - UNINOVE, in the area of concentration "Justice, Company and Sustainability", in Line 1 of Research "Justice and the Efficiency Paradigm".